2021
DOI: 10.1039/d1nr06190a
|View full text |Cite
|
Sign up to set email alerts
|

Rotated domains in selective area epitaxy grown Zn3P2: formation mechanism and functionality

Abstract: Growth process for Zn3P2 nanowires grown on InP at different angles by SAE and formation of rotated domains at (100) and (101) facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 86 publications
(124 reference statements)
2
16
0
Order By: Relevance
“…It has recently been shown that rotated crystallites with interfaces free of dangling bonds can be formed during growth. 50 DFT calculations have shown that the electronic bandgap at these interfaces is significantly decreased compared to the bulk, on the order of 0.1 eV smaller, and new localized acceptor levels are formed. The existence of these 2D defects also appears to have near to no additional energetical cost compared to their absence, though their dependence on temperature is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown that rotated crystallites with interfaces free of dangling bonds can be formed during growth. 50 DFT calculations have shown that the electronic bandgap at these interfaces is significantly decreased compared to the bulk, on the order of 0.1 eV smaller, and new localized acceptor levels are formed. The existence of these 2D defects also appears to have near to no additional energetical cost compared to their absence, though their dependence on temperature is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the nanostructure is a function of the shape of the hole. Nanopyramids are the result for circular holes, while nanowires, or even nanowire networks, are achieved from elongated slits as shown in Figure . However, these shapes are only observed after a couple of intermediate stages. The intermediate morphology as zinc phosphide outgrows the hole depends on the relative surface energies of the dominating facets, namely, (001), (112), and (101).…”
Section: Growth and Crystalline Propertiesmentioning
confidence: 99%
“…The interface between the indium phosphide substrate and zinc phosphide was investigated using HR-TEM and AC HAADF-STEM of FIB lamellae and did not include any misfit dislocations. , The interface roughness observed was due to non-optimized pattern etching. The epitaxial relationship observed was [001] Zn 3 P 2 /[001] InP , making the vertical growth direction of zinc phosphide the c -axis ([001] Zn 3 P 2 ).…”
Section: Growth and Crystalline Propertiesmentioning
confidence: 99%
See 2 more Smart Citations